EFEKTIVITAS BONGGOL PISANG KEPOK (Musa paradisiaca) UNTUK MENURUNKAN KADAR BESI (Fe) DALAM AIR - Charles Situmorang (JURNAL TECHLINK, 2018)
Water is a major requirement for the people of Indonesia. The source of water that is widely used is groundwater, ie water wells. Caused by increased human and industrial activity, well water can be contaminated with ferrous metals (Fe). To be able to make water as a source of clean water, processing needs to be done. This treatment process can be done by adsorption method. The material used can be utilized from the banana hump (Musa paradisiaca L.) as an adsorbent material. The objective of this study was to determine the decrease of ferro content in water by using dried banana paradisiaca L. (Musa paradisiaca L.). This research is experimental type. The cumulative decrease of ferro content (Fe) from the result of addition of banana bonggol with dose 0,08 gram, 0,1gram, 0,2 gram, 0,3 gram, and 0,4 gram respectively is equal to 16,16%, 17 , 96%, 32.9%, 51.5%, and 57.4%. The maximum result of the reaction is ferro content (Fe) in water decreased to 57,4% for dose 0,4 gram / 100 ml water for 30 minutes. In statistical results, there is significance value of p = 0,000 (á 0,05) or there is influence of various doses of banana stump in decreasing ferro content (Fe) in water.